2007
DOI: 10.1037/0021-9010.92.6.1672
|View full text |Cite
|
Sign up to set email alerts
|

An examination of psychometric bias due to retesting on cognitive ability tests in selection settings.

Abstract: Using a latent variable approach, the authors examined whether retesting on a cognitive ability measure resulted in measurement and predictive bias. A sample of 941 candidates completed a cognitive ability test in a high-stakes context. Results of both the within-group between-occasions comparison and the between-groups within-occasion comparison indicated that no measurement bias existed during the initial testing but that retesting induced both measurement and predictive bias. Specifically, the results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
3
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 45 publications
(62 reference statements)
5
115
3
12
Order By: Relevance
“…After exploratory factor analyses and to analyze whether the SAQ has a stable and consistent factor structure, we analyzed configural and metric invariance (Lievens, Reeve, & Heggestad, 2007;Vandenberg & Lance, 2000). For configural invariance (whether the series of items reflects the same latent construct in the diverse groups), we used Tucker's congruence coefficient (r c ), following the recommendations of Jensen (1998, pp.…”
Section: Discussionmentioning
confidence: 99%
“…After exploratory factor analyses and to analyze whether the SAQ has a stable and consistent factor structure, we analyzed configural and metric invariance (Lievens, Reeve, & Heggestad, 2007;Vandenberg & Lance, 2000). For configural invariance (whether the series of items reflects the same latent construct in the diverse groups), we used Tucker's congruence coefficient (r c ), following the recommendations of Jensen (1998, pp.…”
Section: Discussionmentioning
confidence: 99%
“…But while scores may be rising across test administrations, the actual ability level is assumed to be relatively stable. From a psychometric point of view, several researchers have shown that retesting induces measurement bias that makes it difficult to compare initial test and retest scores (e.g., Lievens, Reeve, & Heggestad, 2007). Individual test takers are therefore expected to make assessments that are affected by a number of psychometric problems, the concepts of which are difficult to understand for nonexperts.…”
Section: Critical Aspects Of the Present Meta-analysismentioning
confidence: 99%
“…Hembree (1988) reported the effect of test-skills training on actual test performance to be an r equivalent of .13, and Ergene (2003) reported an r equivalent of .21. Please note, we are not suggesting that practice effects are g-loaded (see, Lievens, Reeve, & Heggestad, 2007;te Nijenhuis et al, 2007). Rather, we are simply noting that g tends to be correlated with learning outcomes in all domains, we thus assume that in the context of test-skills training, g would also be related to skill/knowledge acquisition.…”
Section: G-test Familiarity Relationship (R Gf )mentioning
confidence: 92%